THE IMPACT OF CORPORATE GOVERNANCE MECHANISM ON THE ASYMMETRIC INFORMATION (Empirical Studies on Listing Companies in Indonesian Capital Market The Period of 2004th â 2007th) - Purwanti, Titik (KIAT BISNIS, 2013)
This research aims to analyze the impact of Corporate Governance mechanism onasymmetric information. Corporate Governance mechanism is the subject which protect investorfrom asymmetric information. The sampling method in this research uses purposive samplingwhich selected sample by the criteria. They are companies which the 10th highest rank of IICGfrom 2004-2007. The analysis used descriptive statistics, classic assumption test and multipleregression analysis. The result shows the Corporate Governance mechanism has the significantimpact on asymmetric information. The Corporate Governance index and managerial ownershiphave negative impact on asymmetric information. It shows that the increasing of CorporateGovernance index and managerial ownership will decrease the asymmetric information. Theinstitutional ownership board of commisioner composition and size have not negative impact onasymmetric information significantly.Keywords : Corporate Governance Mechanism, Corporate Governance Index, Asymmetricinformation